Socio-Demographic Characteristics of Blood Donor in a Tertiary Care Specialized Hospital (Bangladesh Journal of Medicine, 2021)
Background: Blood donors are the backbone of a transfusion service. To ensure a safe and appropriate transfusion service, donor demography is to be optimized for proper strategic management. The purpose of this study was to assess the socio-demographic profile of blood donors to make targets for national interventions and to promote blood donation.Methods: This descriptive type cross sectional study was conducted in Transfusion Medicine department of Popular Medical College Hospital from 1st January 2015 to 30th June 2018. All the blood donors who came to donate blood in this department were included in this study. Their signed consent was obtained to include in this study with their socio-demographic determinants. Frequency, percentage and p value